Non-linear association of years of experience and burnout among nursing staff: a restricted cubic spline analysis - Liao, Tanghong; Liu, Yufei; Luo, Wenqun; Duan, Zhizhou; Zhan, Kangmin; Lu, Hongjian; Chen, Xiangfan (Frontiers in Public Health, 2024)
Background Occupational burnout is intricately linked to a spectrum of physical disorders encompassing respiratory, cardiovascular, and gastrointestinal conditions, as well as manifestations such as headaches, type 2 diabetes, elevated cholesterol levels, chronic fatigue, and muscle pain. Despite this association, there remains a paucity of research on the specific risk factors contributing to burnout among nurses in China. Methods This cross-sectional study utilized convenience sampling to recruit participants, with data analyzed from 1,774 nurse staffs. Psychosocial traits were assessed using the Three-Item Loneliness Scale for loneliness, the Generalized Anxiety Disorder 7-item scale (GAD-7) for anxiety symptoms, the 9-item Patient Health Questionnaire (PHQ-9) for depressive symptoms, the Connor Davidson Resilience Scale–10 item (CDRISC-10) for resilience, and the Maslach Burnout Inventory-Human Service Survey (MBI-HSS) for burn out. Restrictive cubic spline analysis to investigate the dose-response relationship between years of experience and burn out. Multivariate linear regression was employed to investigate the relationship between burnout and various risk factors. Results After controlling for basic demographic variables, good sleep quality was associated with a reduction in emotional exhaustion (β = −0.307, p < 0.001), while loneliness (β = 1.334, p < 0.001), depressive symptoms (β = 0.896, p < 0.001), and anxiety symptoms (β = 0.504, p < 0.001) were significantly associated with increased emotional exhaustion. Moreover, higher levels of resilience were positively associated with personal accomplishment (β = 0.635, p < 0.001). Regarding depersonalization, loneliness (β = 0.577, p < 0.001), depressive symptoms (β = 0.429, p < 0.001), and anxiety symptoms (β = 0.152, p < 0.01) were found to increase its level. Conversely, good resilience was associated with a decrease in depersonalization (β = −0.069, p < 0.001). The non-liner association between year of experience and emotional exhaustion was significantly (p < 0.05). Conclusion Our findings revealed that significant risk factors contributing to burnout among nursing staff including bad sleep quality, loneliness, lower level of resilience, anxiety symptoms, depressive symptoms. Moreover, a nonlinear correlation between years of experience and the likelihood of experiencing emotional exhaustion was exist.